Cohesion in Kecil-Kecil Punya Karya - Cindy Anna Damayanti; Ernie Diyahkusumaning Ayu Imperiani (Universitas Pendidikan Indonesia (UPI), 2020)
Children need to create cohesion in their writings since it is an important aspect of good writing. Thus, this study aims to analyze cohesion in children’s writing in terms of the use of cohesive devices. Using Halliday and Hasan’s (1976) theory of cohesion, this study analyzes the type of cohesive devices used in stories written by children and describe the function of the cohesive devices. The data were collected from three stories written by three different children in a book titled ‘Rahasia Cempaka’. It is a collection of short stories included in Kecil-Kecil Punya Karya project published by Mizan. The three stories are ‘Sejuta Maaf Tebusan Perjanjian’, ‘Isi Hati Seorang Siswa’, and ‘Solusi Terbaik untuk Anak Paling Baik’. In terms of the type of cohesive devices used, there are four out five types of cohesive devices found in the stories. The types of cohesive devices used are reference, conjunction, substitution, and ellipsis. Personal Reference came out as the most dominant cohesive devices used by children in their writings with 52.73%, while nominal subtitutions came out as the least with 0.15% occurrences. In addition, in terms of its function, the cohesive devices found in the stories show that children use the cohesive devices in accordance with their functions to create a cohesive and a comprehensible text. It may indicate the children have good writing abilities and have awareness regarding creating cohesive text.Keywords: children’s writing, cohesion, cohesive devices